Effect of Calcination on Microstructure Development and Properties of Hydroxyapatite Powders Extracted from Human and Bovine Bones. Issue 1 (2nd January 2019) - Öksüz, Kerim Emre; Kilinç, Seyran; Özer, Ali
ABSTRACT: This study represents a comprehensive discussion of hydroxyapatite (HAp) formation from human and bovine bones. The phase formation and surface morphologies of prepared HAp powders were determined by XRD and SEM analyses, respectively. TEM was employed to understand the internal compositions with high magnifications and particle size. FT-IR characterizations provided information about molecular interactions and structures. In order to understand the effect of heat treatment at different temperatures and ultimately to get the desired morphology/particle size of the HAp powders derived from human and bovine, the powder samples were calcined at 700° to 1100°C with an interval of 100°C. At 700°C, the organic components were removed and finally, a carbonate apatite was obtained. The degree of crystallinity and crystallite size were noticed to increase progressively with calcination temperature. The overall results showed that the calcination temperature highly influenced the properties of HAp powders derived from human and bovine bone samples. As expected, higher temperatures led to more pure form of HAp with higher degree of crystallinity, larger crystallite size, and a less porous structure. Besides, the human bone structure, in contrary to the bovine bone, did not show temperature sensitivity by means of crystallite size increase. GRAPHICAL ABSTRACT: